Citrus Carotenoid Extracts Exert Anticancer Effects through Anti-Proliferation, Oxidative Stress, and Mitochondrial-Dependent Apoptosis in MCF-7 Cells - Juanjuan Wei; Yurong Li; Zimao Ye; Yi Li; Zhiqin Zhou (Foods, 2023)
Citrus is a globally popular fruit crop that contains bioactive compounds with numerous health benefits. Carotenoids are one of the main bioactive compounds present in citrus pulp. They possess exceptional antioxidant and anticancer properties, making them potentially effective in the prevention and treatment of breast cancer. Different citrus species, identified as ZMPG, DFGJ, NFMJ, XY, and ZHQC, were studied for their antioxidant activity and anticancer activity. XY had the highest total carotenoid content (75.30 µg/g FW), and ZHQC (ZH) had the lowest carotenoid content (19.74 µg/g FW). The composition of NFMJ, ZMPG, and DFHJ consisted of the most abundant number of carotenoids, while XY only had three types. The antioxidant capacity of the carotenoid extracts was evaluated, and ZH and DFHJ were identified as good sources of antioxidants. XY and ZH significantly inhibited cell proliferation, migration, and arresting cells during the G0/G1 phase. XY and ZH enhanced the accumulation of reactive oxygen species (ROS); reduced mitochondrial membrane potential (MMP); reduced the activities of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), and peroxidase (POD); decreased glutathione (GSH) levels; and increased the malonaldehyde (MDA) content. Apoptosis occurred through the mitochondrial-mediated pathway through the up-regulation of BAX, caspase-3, and caspase-9 and the down-regulation of Bcl-2. In this study, the carotenoid-rich extracts of citrus pulp were found to induce oxidative stress through their pro-oxidant potential and regulate cell apoptosis in MCF-7 cancer cells. These results indicate that citrus carotenoids act as pro-oxidants and have the potential to be utilized for the development of anti-breast cancer products.